Pengaruh Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan To Deposit Ratio (LDR) Dan Biaya Operasional Pendapatan Operasional (BOPO) Terhadap Return On Asset (ROA) Pada Bank Perkreditan Rakyat (BPR) di Kota Batam - Agung Joni Saputra; Ria Angriani (Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Operational Costs Operating Income (BOPO) on Return on Asset (ROA) of rural banks in Batam City. Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Operational Costs Operating Income (BOPO) and Return on Asset (ROA) are measured from the financial statements provided on Otoritas Jasa Keuangan (OJK) website. The population used in this study was rural banks in Batam City period 2017-2021. This study used 26 companies with purposive sampling as research sample. The analysis technique used is multiple linear regression analysis. The result of this study indicate that partially Non-Performing Loans (NPL), Net Interest Margin (NIM) and Operational Costs Operating Income (BOPO) have a significant effect on Return on Assets (ROA), while the Capital Adequacy Ratio (CAR) and Loan to Deposits Ratio (LDR) have no significant effect on Return on Assets (ROA). Simultaneously, Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposits Ratio (LDR), and Operational Costs Operating Income (BOPO) have a significant effect on Return on Assets (ROA).